Modeling monopoly money: Government as the source of the price level and unemployment - Sam Levey (Levy Economics Institute of Bard College, 2021)
Many of the claims put forth by Modern Monetary Theory (MMT) center around the state's monopoly over its own currency. In this paper I interrogate the plausibility of two claims: 1) MMT's theory of the price level - that the price level is a function of prices paid by government when it spends - and 2) the claim that the cause of deficient effective demand is the state's failure to supply government liabilities so as to meet the demand for net financial assets. I do so by building a model of "monopoly money" capable of producing these two outcomes.
Keywords: E4; E62; B52; D42; 330; Modern Monetary Theory; Price Level; Monopoly Money; Durapoly; Deficient Effective Demand